98.5k views
3 votes
If g (x)= x+1/x-2 and h(x) =4-c, what is the value of (g•h)(-3)?

If g (x)= x+1/x-2 and h(x) =4-c, what is the value of (g•h)(-3)?-example-1

2 Answers

7 votes

Answer:

Explanation:

g(h(-3)) = g(7)

As h(x)= 4-x so h(-3) = 4+3=7

(g•h)(-3)= g(7) = 7+1/7-2= 8/5

User Rajitha Bandara
by
4.5k points
1 vote

Answer:


g(h(-3)) = (8)/(5)

Explanation:

Given:


g(x)=(x+1)/(x-2) \\


h(x)=4-x

Find
g(h(-3))

What this problem is asking is find the value of
h(-3) and then put that answer into
g(x).

Let's find
h(-3).


h(x)=4-x\\h(-3)=4-(-3)\\h(-3)=7

Now that we found that
h(-3) is equal to 7, we put the value of 7 into
g(x).


g(x)=(x+1)/(x-2)\\g(7)=(7+1)/(7-2) \\g(7)=(8)/(5)

Our final answer is


g(h(-3)) = (8)/(5)

User Mark Stephens
by
5.1k points